Growth Performance and Digestive Enzyme Activity of Broiler Fed with Microwaved Flaxseed Flour (Linum usitatissimum) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
This research aimed to evaluate the effect of the use of microwaved flaxseed flour as broiler feed on the growth performance and digestive enzyme activity. The material used was 200 a-day-old chicks strain Lohmann MB Platinum. The method of this research was in vivo feeding trial using a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments included the use of flaxseed flour with levels of 0% (T0), 2.5% (T1), 5% (T2), 7.5% (T3), and 10% (T4). The variables measured were feed intake, body weight gain, feed conversion ratio, mortality, amylase, and protease activity. The data obtained were analyzed by Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). The result showed that the treatments highly significant (p